ELAVL1‐dependent SOAT2 exacerbated the pancreatitis‐like cellular injury of AR42J cells induced by hyperstimulation with caerulein - Yu‐Jing Sun; Hua‐Ying Chen; Xiao‐Qin Lai (Kaohsiung Journal of Medical Sciences, 2025)
Abstract Pancreatitis is a severe inflammatory condition characterized by damage to the pancreas. Sterol o‐acyltransferase 2 (SOAT2) has been reported to aggravate acute pancreatitis, however, the underlying mechanism remains to be elucidated. Rat pancreatic exocrine cells (AR42J) were treated with caerulein to induce pancreatitis‐like cellular injury. Cell viability was determined using a cell counting kit‐8 (CCK‐8) assay, while cell proliferation was analyzed through a 5‐Ethynyl‐2′‐deoxyuridine assay. Cell apoptosis was measured using flow cytometry, and enzyme‐linked immunosorbent assays were performed to detect levels of pro‐inflammatory cytokines IL‐6 and TNF‐α. Additionally, Fe2+ levels were analyzed using a colorimetric assay kit, reactive oxygen species (ROS) levels were assessed with a Cellular ROS Assay kit, and lipid peroxidation was measured using a malondialdehyde assay kit. Glutathione levels were analyzed with a detection assay. Protein and mRNA expression were evaluated through western blotting and quantitative real‐time polymerase chain reaction, respectively. Furthermore, an RNA immunoprecipitation assay was conducted to investigate the association between ELAV‐like RNA binding protein 1 (ELAVL1) and SOAT2. Actinomycin D assay was performed to explore the effect of ELAVL1 depletion on the transcript stability of SOAT2 mRNA. SOAT2 and ELAVL1 expression were upregulated in caerulein‐exposed AR42J cells. Caerulein treatment induced pancreatitis‐like cellular apoptosis, inflammatory response, ferroptosis, and cell proliferation inhibition. Silencing of SOAT2 protected against caerulein‐induced AR42J cell injury. Moreover, ELAVL1 stabilized SOAT2 mRNA expression in AR42J cells. SOAT2 overexpression attenuated the effects induced by ELAVL1 silencing in caerulein‐exposed AR42J cells. Additionally, ELAVL1 knockdown activated the NRF2/HO‐1 pathway by downregulating SOAT2 expression in caerulein‐exposed AR42J cells. SOAT2 silencing protected AR42J cells from caerulein‐induced injury by inactivating the NRF2 pathway. In conclusion, ELAVL1‐dependent SOAT2 exacerbated pancreatic exocrine cell injury by inactivating the NRF2/HO‐1 pathway in pancreatitis. These findings provide new insights into the molecular mechanisms underlying pancreatitis and offer potential therapeutic targets for the treatment of this condition.